Prospecting laccase-producing wood-decaying fungi from the UPR peat swamp forest, Central Kalimantan - Lumbantoruan, Lidia Amelia; Arum, Diah Panjar; Charles, Adrian; Togatorop, Hanna Esrani; Suni, Muhammad Ikhwan; Rahayu, Putri; Krissilvio, Eka Jhonatan; Haryono, Agus; Agnestisia, Retno (Institut Teknologi Bandung, 2026)
Tropical peat forests of Kalimantan harbor diverse wood-decaying fungi with strong ligninolytic potential, yet their functional enzymatic characteristics remain poorly documented. This study prospectively examined the physiological expression of laccase production in native fungi isolated from the Universitas Palangka Raya peat swamp forest, Central Kalimantan. Three stable pure cultures were obtained: MIPA 2 (Ganoderma sp.), MIPA 4 (Trametes sp. 1), and MIPA 8 (Trametes sp. 3). All isolates produced extracellular laccase but showed clear differences in growth and enzyme productivity. Growth analysis revealed distinct radial expansion rates, with MIPA 2 exhibiting the fastest mycelial growth (13.64 mm/day). The faster radial growth of MIPA 2 suggests higher metabolic activity and biomass formation, which may contribute to its superior laccase production compared to the other isolates. Qualitative screening on syringaldazine-amended PDA also confirmed extracellular laccase activity in all isolates, with activity levels ranging from weak (+) to strong (+++). Quantitative assays in potato dextrose broth and modified glucose–peptone medium revealed strong nutrient-dependent regulation of laccase biosynthesis, with MIPA 2 reaching 93.71 U/L on day 21. The pronounced stimulation by organic nitrogen indicates ecological adaptation to acidic, nutrient-limited peat environments and distinguishes these isolates from many previously reported Ganoderma and Trametes strains that typically require external inducers for high activity. These findings demonstrate that peat swamp ecosystems represent not only a geographic source but also a reservoir of fungi with distinct ligninolytic expression profiles and potential biotechnological relevance.